Pelatihan Pengembangan Potensi Wisata Di Desa Waara Kabupaten Buton Tengah - Fajar Maulana, Harry; Hastuti, Hastuti; Taqwa Utami, Nur; Isram, Safarina (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2022)
Waara Village, Central Buton Regency, is one of Indonesia's villages with tourism potential that has not been optimally developed. This activity aims to examine the training of tourism potential development in Waara Village and its impact on sustainable tourism management. The training method used in developing tourism villages is a participatory approach, where the community is actively involved in planning and implementing tourism village development programs. Participation and participation of the community and stakeholders are also very important in developing sustainable tourism and preserving the environment and local culture. After identifying tourism potential, the next step is to strengthen the capacity of the community through training and development of tourism management skills that can be done through extensive training by various institutions, such as the government, NGOs, and academic institutions, which can encourage the development of tourism potential and stimulate local economic growth.